Answer :

Given: 1 – (x – 2) – [(x - 3) – (x - 1)] = 0

Opening the brackets we get,


1 - x + 2 - [x - 3 - x + 1] = 0


 3 - x - x + 3 + x - 1 = 0


3 - x + 2 = 0


5 - x = 0


-x = -5 (transposing 5 to RHS)


x = 5


Hence value of x is 5.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Solve each of theRD Sharma - Mathematics